On the slow quenching of ℳ* galaxies: heavily obscured AGNs clarify the picture. Issue 4 (23rd May 2020) - Moutard, Thibaud; Malavasi, Nicola; Sawicki, Marcin; Arnouts, Stéphane; Tripathi, Shruti
ABSTRACT: We investigate the connection between X-ray and radio-loud active galactic nuclei (AGNs) and the physical properties of their evolved and massive host galaxies, focussing on the mass-related quenching channel followed by M^(10^10.6 M_) galaxies in the rest-frame NUV– r versus r – K (NUVrK) colour diagram at 0.2 < z < 0.5. While our results confirm that (1) radio-loud AGNs are predominantly hosted by already-quenched and very massive (M_*10^11 M_ ) galaxies, ruling out their feedback as a primary driver of M^ galaxy quenching, we found that (2) X-ray AGNs affected by heavy obscuration of their soft X-ray emission are mostly hosted by M^ galaxies that are in the process of quenching. This is consistent with a quenching scenario that involves mergers of (gas-poor) M^ galaxies after the onset of the quenching process, i.e. a scenario where M^ galaxy mergers are not the cause but rather an aftermath of the quenching mechanism(s). In that respect, we discuss how our results may support a picture where the slow quenching of M^ galaxies happens due to halo–halo mergers along cosmic filaments.